An iteration technique and commutativity of rings - H. A. S. Abujabal; M. S. Khan (International Journal of Mathematics and Mathematical Sciences)
Through much shorter proofs, some new commutativity theorems for rings with unity have been obtained. These results either extend or generalize a few well-known theorems. Our method of proof is based on an iteration technique.